Updating the role of matrix metalloproteinases in mineralized tissue and related diseases - Tokuhara, Cintia Kazuko; Santesso, Mariana Rodrigues; Oliveira, Gabriela Silva Neubern De; Ventura, Talita Mendes Da Silva; Doyama, Julio Toshimi; Zambuzzi, Willian Fernando; Oliveira, Rodrigo Cardoso De (Faculdade De Odontologia De Bauru - USP, 2019)
Abstract Bone development and healing processes involve a complex cascade of biological events requiring well-orchestrated synergism with bone cells, growth factors, and other trophic signaling molecules and cellular structures. Beyond health processes, MMPs play several key roles in the installation of heart and blood vessel related diseases and cancer, ranging from accelerating metastatic cells to ectopic vascular mineralization by smooth muscle cells in complementary manner. The tissue inhibitors of MMPs (TIMPs) have an important role in controlling proteolysis. Paired with the post-transcriptional efficiency of specific miRNAs, they modulate MMP performance. If druggable, these molecules are suggested to be a platform for development of “smart” medications and further clinical trials. Thus, considering the pleiotropic effect of MMPs on mammals, the purpose of this review is to update the role of those multifaceted proteases in mineralized tissues in health, such as bone, and pathophysiological disorders, such as ectopic vascular calcification and cancer.
Keywords: Extracellular matrix; Matrix metalloproteinases; Bone; Vascular calcification; Extracellular vesicles